Central Bank boards around the world: Why does membership size differ? - Helge Berger; Volker Nitsch; Tonny Lybek (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2008)
This paper analyzes empirically differences in the size of central bank boards (or monetary policy committees) across countries. We discuss the possible determinants of a board's size. The empirical relevance of these factors is examined using a new dataset that covers the de jure membership size of 84 central bank boards at the end of 2003. We find that larger and more heterogeneous countries, countries with stronger democratic institutions, countries with floating exchange rate regimes, and independent central banks with more staff tend to have larger boards.
Keywords: E52; E58; E61; 330; Committee; council; governance; decision making; monetary policy; Geldpolitik; Zentralbank; Governance-Ansatz; Entscheidung; Welt